Svätopluk as a Historical Figure: An Attempt at Reconstruction - HOMZA, Martin (Studia Universitatis Babeș-Bolyai Historia, 2025)
The article is part of a larger monograph on Svätopluk I, which maps Svätopluk I as a) a historical figure; b) European historiography on the most successful ruler of the Western Slavs in the 9th century, and c) the image (imago) of the ruler as retrospectively created by medieval writings across Europe. In this text, Martin Homza focuses on presenting Svätopluk as a historical figure based on existing sources and available metahistorical texts. During his reign, the first Moravian archbishopric and bishopric in Nitra were established. At the same time, a network of church administration was created, and Christianity gained significant ground in the rest of Europe, which had been pagan until then. This expansion was made possible by internal (political and economic stabilization of his personal power) and external factors, the most important of which was Svätopluk’s pragmatic policy towards the East Frankish rulers. This brought him not only multiple recognition of his de facto rule, but also acceptance into the wider Carolingian family. However, the most important recognition came from the papacy of the time, which accepted him (and with him his empire) as its only son – unicus filius – under its patronage. This was a historical precedent for the creation of what we now call Central Europe, and in the plans of the popes of the time, it was contrasted with the Regnum Teutonicorum and called the Kingdom of the Slavs – Regnum Sclavorum. However, these bold plans suffered in the last two years of Svätopluk’s reign when he allowed himself to be drawn into a military confrontation with his compater Arnulf, the East Frankish ruler. The unexpected death of Svätopluk I, the subsequent unfortunate reign of his sons, as well as the invasions of the Old Hungarian tribal confederation and the Bavarians, brought about the temporary collapse of this project. The restoration of the kingdom on the Middle Danube under the patronage of St. Peter, this time with a new dynasty, came around the year 1000. Rezumat: Articolul este parte dintr-o monografie mai mare, în pregătire, despre Svätopluk I. Lucrarea îl urmărește pe Svätopluk I ca personalitate istorică, analizează istoriografia despre cel mai de succes stăpânitor al slavilor apuseni, respectiv urmărește imaginea lui, așa cum au conturat-o retrospectiv scrierile medievale din Europa. În acest studiu, pe baza surselor și a textelor metaistorice avute la dispoziție, autorul se concentrează asupra prezentării lui Svätopluk ca personalitate istorică. În timpul stăpânirii sale a luat naștere prima arhiepiscopie a Moraviei și episcopia de la Nitra. În același timp, s-a constituit o rețea a administrației ecleziastice, iar creștinismul s-a impus într-o mare măsură într-o parte, până atunci păgână, a Europei. Această expansiune a fost posibilă datorită unor factori interni (stabilizarea politică și economică a puterii sale personale) și externi; dintre aceștia din urmă, cel mai important factor a fost politica pragmatică a lui Svätopluk față de regii franci de răsărit. Această politică i-a adus recunoașterea de câteva ori a guvernării sale, dar și primirea în familia în sens larg a Carolingienilor. Oricum, cea mai importantă apreciere a venit din partea Papalității, care l-a luat pe domnitor (și împreună cu acesta întregul său imperiu) sub patronajul său în calitate de unic fiu – unicus filius. Acesta a fost un precedent istoric pentru crearea a ceea ce astăzi numim Europa Centrală; în planurile papale, era numit Regatul Slavilor – Regnum Sclavorum, în contrast cu Regnum Teutonicorum. Aceste proiecte curajoase au avut de suferit în ultimii doi ani de domnie ai lui Svätopluk, atunci când s-a lăsat antrenat într-o confruntare militară cu compater-ul său Arnulf, stăpânitorul franc de răsărit. Moartea neașteptată a lui Svätopluk I, domnia nefericită a fiilor săi, precum și atacurile uniunii de triburi ale vechilor maghiari și ale bavarezilor au dus la prăbușirea temporară a acestui proiect. Restaurarea proiectului regatului de la Dunărea de mijloc, sub patronajul Sfântului Petru, dar sub o nouă dinastie, s-a produs în jurul anului 1000. Cuvinte-cheie: Svätopluk, Imperium Christianum, Papalitate, Moravia, Regnum Sclavorum, Europa Centrală.